Femoral neck and shaft structure in Homo naledi from the Dinaledi Chamber (Rising Star System, South Africa). Issue 133 (August 2019) - Friedl, Lukas; Claxton, Alex G.; Walker, Christopher S.; Churchill, Steven E.; Holliday, Trenton W.; Hawks, John; Berger, Lee R.; DeSilva, Jeremy M.; Marchi, Damiano
Abstract: The abundant femoral assemblage of Homo naledi found in the Dinaledi Chamber provides a unique opportunity to test hypotheses regarding the taxonomy, locomotion, and loading patterns of this species. Here we describe neck and shaft cross-sectional structure of all the femoral fossils recovered in the Dinaledi Chamber and compare them to a broad sample of fossil hominins, recent humans, and extant apes. Cross-sectional geometric (CSG) properties from the femoral neck (base of neck and midneck) and diaphysis (subtrochanteric region and midshaft) were obtained through CT scans for H. naledi and through CT scans or from the literature for the comparative sample. The comparison of CSG properties of H. naledi and the comparative samples shows that H. naledi femoral neck is quite derived with low superoinferior cortical thickness ratio and high relative cortical area. The neck appears superoinferiorly elongated because of two bony pilasters on its superior surface. Homo naledi femoral shaft shows a relatively thick cortex compared to the other hominins. The subtrochanteric region of the diaphysis is mediolaterally elongated resembling early hominins while the midshaft is anteroposteriorly elongated, indicating high mobility levels. In term of diaphyseal robusticity, the H. naledi femur is more gracile that other hominins and most apes. Homo naledi shows a unique combination of characteristics in its femur that undoubtedly indicate a species committed to terrestrial bipedalism but with a unique loading pattern of the femur possibly consequence of the unique postcranial anatomy of the species.